The overuse of clonazepam: pharmacist's role in the conscientious use of the drug (Research, Society and Development, 2021)
In recent years, the search for and consumption of psychoactive drugs has increased gradually. Within this list, the drug clonazepam is the most sought after in Brazilian pharmacies. Despite these drugs being cited in the literature as one of the safest, they hide serious problems in their management, because the difficulties inherent to a dependency situation do not prevail over the benefits and often go unnoticed due to the complexity of the situations involved in the treatment of patients. The objective of this study was to highlight the abusive use of clonazepam in conjunction with the role of the pharmaceutical professional in this scenario. The methodology was a systematic literature review with data survey with 19 bibliographic references in the period from 2010 to 2020 in the Bases of scientific research in the health area. Through this work, the pharmacological characteristics, indications, uses and cons of clonazepam were evidenced, as well as the ease of its abusive use and possible harmful effects of its dependence. The role of the pharmacist is essential due to his knowledge and attributions in order to warn users about the risks of potential side effects and high dependency rates.